Development and Evaluation of a Reliable Medication Management Self-Assessment Checklist - Brian Isetts; Kristine Talley; Ann Brearley (University of Minnesota Libraries Publishing, 2024)
An ability to effectively self-manage medications is the result of several factors influencing a person's decision to take medications. The need for new approaches to medication self-management are evident in the persistent trends of ineffective and unfortunate medication use consequences, referred to as drug-related morbidity and mortality.  Fortunately, pioneering initiatives have emerged to reshape our approach for developing a rational organizational paradigm so that patients can confidently self-manage medications.      Favorable outcomes of studies pertaining to the delivery of comprehensive medication therapy management services within the practice of pharmaceutical care prompts the question, 'Can patients and family members apply the 4-step pharmacotherapy workup process to better organize their decision-making and confidence in medication self-management?' To answer this question an Effective Medication Self-Management Toolkit based on this 4-step process, and a Medication Management Self-efficacy Checklist, were created and evaluated for feasibility, acceptability, and internal consistency reliability.      The first evaluation established the preliminary acceptability and feasibility of the toolkit using a convenience sample of 39 residents of independent living facilities in focus group sessions. All participants indicated they perceive that the 4-step process can help individuals successfully self-manage medications. At the conclusion of the focus group sessions, all 39 participants completed the 7-item post-session checklist. This paper presents the second evaluation to establish the internal consistency reliability of the toolkit's Medication Management Self-efficacy Checklist using Cronbach's alpha. There was good internal consistency of the self-efficacy checklist with a Cronbach's alpha value of 0.82.      This investigation of a novel approach for applying the 4-step pharmacotherapy assessment process by patients suggests that it is feasible and acceptable to use, and that the medication self-efficacy checklist provides a reliable and useful measure of a patient's confidence in self-managing medications.